Penatalaksanaan Holistik Pasien Wanita Usia 65 Tahun dengan Kanker Payudara Post Mastektomi melalui Pendekatan Keluarga di Wilayah Puskesmas Kampung Sawah - Arifah Putri Desenia; Winda Trijayanthi Utama (Fakultas Kedokteran Universitas Lampung, 2025)
Breast cancer is the most common type of cancer and attacks women throughout the world. Breast cancer is a malignancy in breast tissue that can originate from the ductal epithelium or lobules. In Indonesia, more than 80% of cases are found to be at an advanced stage, where treatment is difficult so understanding is needed regarding prevention, early diagnosis, curative and palliative treatment as well as rehabilitation, so that treatment can be done optimally. The purpose of this paper is to identify internal and external risk factors, clinical problems, as well as holistic and comprehensive management according to a family doctor's approach through a family, patient-centered and community-oriented approach. The study conducted was in the form of a case report. Data was obtained through alloanamnesis, physical examination and home visits. Assessment based on initial and final holistic diagnosis quantitatively and qualitatively. Patient Mrs. J, 65 years old, lives with his younger sibling. The patient came to Kampung Sawah Puskesmas with the aim of changing of the dressing wound from post mastectomy operation and complained of pain in the surgical wound. The patient’s clinical diagnosis was breast cancer. Interventions are given pharmacological dan non pharmacological. There is an increase in patient and family’s knowledge regarding the patient’s condition and there is an improvement of patient’s condition.